PERBAIKAN KEBIJAKAN PENGENDALIAN PERSEDIAAN JUST IN TIME KOMPONEN PRODUK MAIN FLOOR SIDE LH PADA PT GAYA MOTOR - Istiqomah, Bella Suciana; Marie, Iveline Anne (Universitas Muhammadiyah Surakarta, 2015)
PT . Gaya Motor is a manufacturing company that is engaged in the assembly and production of automotive components incorporated in the group of PT Astra International.Perusahaan implement inventory control system Just In Time.Kanbanâs supplier with safety stock of 0.5 days plus a safety stock of 0.5 extra days beyond the kanban. The study was conducted on the material supply products Main Floor Side LH SA - 001 , SA - 002 , SA - 003 , SA - 004 , SA - 005 , SA - 006 , SA - 007 , SA - 008 and SA - 009. Problems faced by the company are the high amount of inventory caused by inaccurate inventory systems and fault current in raw material procurement procedures. The purpose of this study was to evaluate the companys current inventory control system and propose improvements inventory control system that can minimize inventory costs compared to the cost of inventory at the companys current inventory system.Kanban inventory method supplier company currently has a total cost of inventory of Rp 318.861.462,00. Supplier kanban inventory control methods with safety stock kanban 0.1 days has a total cost of inventory of Rp 158.703.378,00. Inventory control methods Two - Bin Replenishment has a total inventory cost of Rp 98.497.214,00. From the results of these calculations, the minimum inventory cost obtained by using the method of inventory Two - Bin Replenishment, and made proposals related to changes in inventory control system.